EFEKTIFITAS PEMBERIAN AROMATERAPI LEMON TERHADAP IBU HAMIL TRIMESTER PERTAMA DENGAN EMESIS GRAVIDARUM - Regina Silaen, Kartika; Mariyana, Mariyana; Darma, Abdi (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
Pregnancy is a physiological process that causes physical, mental and social changes and is often accompanied by discomfort, especially nausea and vomiting in the first trimester caused by an increase in the hormones estrogen and HCG. One therapy that is safe and can be given to pregnant women who experience emesis gravidarum is by providing lemon aromatherapy. The aim of this research is to determine the effectiveness of lemon aromatherapy in first trimester pregnant women with emesis gravidarum at the Independent Practice of Midwife Lusia Herawaty, S.Keb in 2024. This research uses a Quasi Experimental research design in one group (one group pre test post test). The sampling technique used purposive sampling with a sample size of 21 pregnant women and data collection used observation sheets. The results showed that the average frequency of nausea and vomiting before being given lemon aromatherapy was 8.62 and after being given lemon aromatherapy was 3.48, p value = 0.000 (P < 0.05). Based on statistical results, it can be concluded that there is effectiveness of lemon aromatherapy in reducing emesis gravidarum in first trimester pregnant women at PMB Lusia Herawaty, S.Keb in 2024. It is recommended that pregnant women who experience emesis gravidarum or nausea and vomiting can consume lemon aromatherapy to reduce the frequency of nausea and vomiting.